Dynamic modelling and sensitivity analysis of a tubular SOFC fuelled with NH3 as a possible replacement for H2 - Hajimolana, Sayed Ahmad; Hussain, Mohd Azlan; Daud, Wan Mohd Ashri Wan; Chakrabarti, M.H. (Chemical Engineering Research and Design, 2012)
A dynamic model of an ammonia fed-tubular solid oxide fuel cell (NH 3-SOFC) is developed and presented. The model accounts for diffusion, inherent impedance, transport (heat and mass transfer), electrochemical reactions, activation and concentration polarizations of electrodes and the ammonia decomposition reaction. Sensitivity analyses are conducted upon the effects of design parameters on the fuel cell performance. Dynamic output voltage, fuel-cell-tube temperature and efficiency responses to step changes in the inlet fuel flow pressure with different values of design parameters are discussed. It is found that among the studied parameters, the inner cell tube diameter has the strongest effect on fuel cell efficiency. On the other hand, the influence of cathodic porosity on fuel cell performance and transient response is higher than that of the anodic porosity. The transient response with different sizes of micro and macro-structures is studied and it is observed that changing the fuel cell length has the most effect. Also NH 3-SOFC is compared with H 2-SOFC and it is found that the performance of the former is close to that of the latter thus signifying that ammonia is a suitable fuel for substituting in place of hydrogen.